Identification of reproductive performance in Bali-polled bulls using computer-assisted semen analysis and plasma seminal proteomics - Athhar Manabi Diansyah; Sanstoso Santoso; Herdis Herdis; Muhammad Yusuf; Tri Puji Priyatno; Tulus Maulana; Abdul Latief Toleng; Muhammad Ihsan Andi Dagong; Syahruddin Said; Hikmayani Iskandar; Aeni Nurlatifah; Puji Lestari; et al. (Veterinary World)
Background and Aim: Bali-polled bulls, known for their favorable traits, require advanced reproductive performance analysis to optimize breeding programs. This study aimed to evaluate sperm kinematics and seminal plasma proteomic profiles as biomarkers for sperm motility and fertility in Bali-polled bulls.